L’égalité en matière d’héritage. Jeunes et savoir commun au Maroc - Merieme Yafout (L’Année du Maghreb)
The aim of this article is to highlight the knowledge of a small sample of young Moroccans about the rule of inheritance that allows boys inherit a double portion of their sisters after the death of the father. So I will raise vocabulary, arguments, opinions that these young people develop about this rule. I will consider then how the common knowledge of these young people articulates the different lexicons of « high culture » and the positions vis-à-vis the said rule of inheritance. Moreover, the knowledge that these young people express is also linked to socio-cultural assumption that they manifest as spontaneous discourse, accessible and clear on male / female relations, on family, on the division of social roles, on the place of religion in society. It is a knowleldge organically linked to everyday life which guides the actions and helps to understand the meaning that people give to their actions.